2019
DOI: 10.2147/cmar.s202799
|View full text |Cite
|
Sign up to set email alerts
|

<p>Apolipoprotein M could inhibit growth and metastasis of SMMC7721 cells via vitamin D receptor signaling</p>

Abstract: Objective: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors with high mortality-to-incidence ratios. Apolipoprotein M (ApoM), a member of the apolipoprotein family, is mainly synthesized in the liver, whereas its role in HCC has not been elucidated. Here, we examined the effect of ApoM on the biological behavior of HCC cells and the possible mechanisms. Methods: We used CRISPR/Cas9 technology to knock out ApoM in SMMC7721 cells. Differentially expressed genes before and after ApoM knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Vitamin D enters cells by two pathways: the steroid receptor pathway and the direct entry pathway. Vitamin D receptor (VDR) is a membrane receptor for vitamin D. However, whether VDR is a tumour suppressor or an oncogene remains unclear [27][28][29] . The VDR expressions in cisplatin and vitamin D treatments failed to show significant changes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D enters cells by two pathways: the steroid receptor pathway and the direct entry pathway. Vitamin D receptor (VDR) is a membrane receptor for vitamin D. However, whether VDR is a tumour suppressor or an oncogene remains unclear [27][28][29] . The VDR expressions in cisplatin and vitamin D treatments failed to show significant changes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that VDR plays an important role in cell proliferation, differentiation, angiogenesis and apoptosis. Our previous research found that APOM could upregulate the VDR mRNA level in colorectal cancer cells 11 , and APOM could also affect the biological functions of SMMC772I cells via VDR signalling, such as inhibiting proliferation and metastasis 13 . Thus, we examined the VDR mRNA and protein levels in the TU686 cells of the APOM-OE group and NC group.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, our research demonstrated that APOM can promote the proliferation and invasion of non-small cell lung cancer cells, which is related to the upregulation of S1P-receptor 1 and activation of the ERK1/2 and PI3K/AKT signalling pathways induced by APOM 12 . Furthermore, we reported that APOM can suppress the proliferation and invasion of SMMC7721 cells, a hepatocellular carcinoma line, through VDR pathways 13 . In the present study, we compared the expression of APOM in different types of laryngeal tissues, analysed the biological effects of APOM overexpression on LC cells, and explored the possible mechanisms of APOM in the development of LC.…”
mentioning
confidence: 98%
“…Regardless of its associations with S1P, evidence indicates the beneficial role of apoM in various malignancies [ 88 , 89 ]. Importantly, it was shown that apoM increases the expression of vitamin D receptor in CRC cells [ 90 ].…”
Section: Functional Characteristics Of Hdl Particles In Crcmentioning
confidence: 99%